Hubungan antara Amalan Kepimpinan Instruksional dan Motivasi Kerja Guru TVET - Mohd Shafri, Nur Fatin; Ahmad, Zanariah (Research and Innovation in Technical and Vocational Education and Training, 2025)
This study aims to identify the relationship between principals' instructional leadership practices and teachers' work motivation within the context of Technical and Vocational Education and Training (TVET). The study is grounded in McClelland’s (1978) motivation needs theory which emphasizes the needs for achievement, power and affiliation to identify the components of instructional leadership that influence teachers’ motivation. The primary objectives of this study are to identify the level of instructional leadership practices as perceived by teachers to evaluate the level of work motivation among TVET teachers and to identify relationship between these two variables. The study was conducted in secondary schools within the Batu Pahat district, Johor that involving 246 respondents who teach TVET-related subjects. The results reveal a significant relationship between principals' instructional leadership practices and the work motivation of TVET teachers. Specifically, the dimensions of instructional resource provision and curriculum implementation demonstrate a strong correlation with teachers' work motivation. The findings of this study are anticipated to provide valuable insights for educational administrators, helping to enhance leadership effectiveness and support teachers’ professional development. Ultimately, these improvements are expected to positively influence teachers' motivation, student performance and the overall success of educational institutions.